1996
DOI: 10.1016/s1078-5884(96)80273-5
|View full text |Cite
|
Sign up to set email alerts
|

Computerised tomography findings as a risk factor in carotid endarterectomy: Early and late results

Abstract: A positive CT finding, regardless of congruity of the lesion, should be regarded as an indicator of an increased risk of stroke and death in patients scheduled for carotid surgery, especially in those with asymptomatic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The literature on the influence of CIL on carotid revascularization outcome is discordant. In their analysis of 503 symptomatic patients, Cao et al 14 found, similarly to our study, an incidence of CIL in patients with stroke of 54% and TIA of 33%. Stroke and death in their series were significantly higher in patients with CIL; however, their study considered both ipsilateral and contralateral lesions.…”
Section: Journal Of Vascular Surgerysupporting
confidence: 89%
See 1 more Smart Citation
“…The literature on the influence of CIL on carotid revascularization outcome is discordant. In their analysis of 503 symptomatic patients, Cao et al 14 found, similarly to our study, an incidence of CIL in patients with stroke of 54% and TIA of 33%. Stroke and death in their series were significantly higher in patients with CIL; however, their study considered both ipsilateral and contralateral lesions.…”
Section: Journal Of Vascular Surgerysupporting
confidence: 89%
“…Many retrospective studies have analyzed the influence of the clinical characteristics, such as TIA and stroke, on carotid revascularization outcome 18,19 ; however, one must consider that a significant number of patients with TIA (30%-40%) may present with a CIL and that many patients with a minor stroke (50%) do not have any CIL visible at CT, as shown also in our study. 14 In fact, 18.9% of patients with clinical stroke did not present a CIL at CT, which was instead present in 43% of patients with clinical TIA. Consequently, the evaluation of the type of symptoms is not sufficient to define the extension of brain damage.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 96%
“…However, different data are reported in the literature. Cao et al (27), in their analysis of 503 symptomatic patients, identified CIL in 54% of patients with stroke and 33% of those with TIA. CIL influenced the outcome of CEA in their series: stroke and death were significantly higher in patients with CIL (OR: 6.37; 95% CI, 5.12-7.63).…”
Section: Carotid Revascularization Outcome According To the Presence Of Cilmentioning
confidence: 99%
“…In contrast, "silent" cerebral infarction might be more important for the operative risk of stroke during and immediately after carotid surgery. Some surgeons have reported an extraordinarily high perioperative complication rate (up to 14%) [7,8], whereas others have contested an association [9 -14]. These studies can be criticized, as they were either retrospective or did not include adjustments for patient differences with respect to confounding variables.…”
mentioning
confidence: 99%